Efeito do ácido acético sobre o crescimento e fermentação da levedura Meyerozyma guilliermondii - Perna, Michelle dos Santos Cordeiro (2016)
The viability of technologies that make possible to use all available plant biomass, such as the production of lignocellulosic ethanol, faces challenges as the search for microorganisms capable of fermenting pentoses with high tolerance to inhibitors released in the biomass hydrolysis step, such as acetic acid and furfural. This study aimed to evaluate the metabolizing capacity of pentoses and glucose by a yeast strain of Meyerozyma guilliermondii (CCT7783) in the presence of furfural and acetic acid. The first set of experiments comprised the evaluation of cell growth in a synthetic medium containing acetic acid as the sole carbon source at concentrations of 1.5; 2.5; 4.5; 10.5; 13.5; 16.5 and 19.5 g/L at 30°C, 160 rpm, pH 5.5, with initial concentration of 0.2 g/L of dry mass for a period of 96 hours of incubation. It was also evaluated the effect of pH (3.5 and 5.5) and the initial concentration of dry mass (0.2, 0.5 and 2.5 g/L). The second set of experiments consisted in the evaluation of the effect of furfural (20 and 40 mg/L) and acetic acid (5 and 10 g/L) in the fermentation of pentoses (arabinose and xylose) and glucose, biomass and ethanol production. The yeast M. guilliermondii was able to grow in synthetic medium in all the acetic acid concentrations tested, at pH 5.5. The concentrations of acetic acid evaluated were much higher than those commonly found in hemicellulosic hydrolysates. Growth inhibition occurred in concentrations of acetic acid beyond 10.5 g/L. The initial pH and the initial cell concentration influenced the growth and the acetic acid consumption. In synthetic medium containing glucose, pentoses and acetic acid as carbon sources, the highest specific growth rate was obtained in the treatment with the addition of 5 g/L of acetic acid, which was consumed concomitantly with the pentoses and glucose in all treatments, however the acetic acid was an inhibitor at the concentration of 10 g/L. Furfural inhibited the growth of the yeast in the concentration of 40 mg/L. The ethanol production by M. guilliermondii was lower comparing to the micro-organisms commonly utilized in the fermentation process. The yeast was able to grow and promote the biological detoxification even in the presence of the inhibitors like acetic acid and furfural, showing that the process requires optimization and that the yeast M. guilliermondii may be applied in biotechnological routes for the production of second generation ethanol.